Validation, accuracy and practical use of a power measurement system for cross-country skiing analysis - a pilot study - Kuyienstierna, D.; Hoegstrand, J.; Lai, S.; Gingsjö, H.; Lindinger, S. (Science and Skiing VIII. Book of the 8th International Congress on Science and Skiing, 2020)
Cross-country skiing is a sport with high demands on central and local physical apacity and involves complex biomechanical motion patterns (Saltin 1987, Smith 1992, Mahood et al 2001, Sandbakk & Holmberg 2014). Such factors were investigated in labs, e.g. VO2 tests on ergometers and treadmills (Mahood et al. 2001, Nilsson 2008, Ingjer 1991, Larsson et al. 2002, Holmberg et al. 2008, Bjerkefors et al. 2012). Graded exercise tests have been developed for extraction of intensity zones. Extensive lab-tests have also been carried out to study various biomechanical parameters (Holmberg et al. 2005, Holmberg et al. 2006). In particular for skiing propulsive forces have been investigated based on force plates and pressure soles. Force sensors have also been integrated into ski poles, however, most studies are based on bulky systems not well adapted for field tests under realistic conditions. For field assessment of exercise intensity the most commonly used method is to measure heart rate (HR) which underlies several problems, e.g. day-to-day variations due to various factors. It is also too slow to reflect intensities in anaerobic zones. Hence, there is a strong motivation to develop a light, versatile system usable for realtime field measurements of propulsive pole forces and angles during skiing. This work reports on initial tests with specially designed ski-pole grips with integrated load cells, IMUs, microcontrollers and wireless transmitters, marketed by Skisens AB. The handles enable calculation of mechanical power which can be used for intensity control. Beside power, the handles also provide momentaneous axial pole force and pole angle as unique fingerprints of skiing technique (Bengths et al. 2016). The aim of this work was to validate the developed technology vs. Golden Standard Systems. Kistler force plates was used to validate force and a Qualisys Oqus motion capture System was used to validate pole angles.